Deictic Expressions in the First SONAs of Rodrigo Duterte and Ferdinand Marcos Jr. - Ma. Sophia Pintado; Mark Jayce Cereño; Annalie Librea; Rechie Bejasa; Joemar Turno Minoza (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
This study assumes that former President Rodrigo Duterte and President Ferdinand Marcos Jr. used different types of deixis in their first State of the Nation Address (SONAs). Supporting this assumption is the theory of Deictic Expressions by Stephen Levinson. This study is descriptive qualitative. Findings revealed that former President Duterte and President Marcos Jr. used different types of deixis in their speeches. The most dominant type of deixis used by former President Duterte is personal deixis, which obtained the highest frequency, particularly the pronoun